Production of High-Viscosity Whey Broths by a Lactose-Utilizing Xanthomonas campestris Strain - Schwartz, Robert D. (1985)
Xanthomonas campestris BB-1L was isolated by enrichment and selection by serial passage in a lactose-minimal medium. When BB-1L was subsequently grown in medium containing only 4% whey and 0.05% yeast extract, the lactose was consumed and broth viscosities greater than 500 cps at a 12 s(−1) shear rate were produced. Prolonged maintenance in whey resulted in the loss of the ability of BB-1L to produce viscous broths in whey, indicating a reversion to preferential growth on whey protein, like the parent strain.